Impact of cumulative cisplatin dose and adjuvant chemotherapy in locally-advanced nasopharyngeal carcinoma treated with definitive chemoradiotherapy. (June 2020) - Oliva, Marc; Huang, Shao Hui; Taylor, Rachel; Su, Jie; Xu, Wei; Hansen, Aaron R; Jang, Raymond; Bayley, Andrew; Hosni, Ali; Giuliani, Meredith; Ringash, Jolie; Bratman, Scott V; et al.
Highlights: Adjuvant chemotherapy was associated with OS benefit only in stage IV disease Total CDDP-D >300 mg/m 2 significantly improved 5-year OS in the entire cohort Total and adjuvant CDDP-D were associated with higher OS and RFS in stage IV disease Higher total and adjuvant CDDP-D trended to improve LRC but had no effect on DC Abstract: Background: Both adjuvant chemotherapy and higher cumulative cisplatin dose (CDDP-D) given as part of multimodality therapy for locally-advanced nasopharyngeal carcinoma (LA-NPC) have improved survival in Asian series. We evaluated their impact in a contemporary single-institution Canadian cohort of LA-NPC. Methods: Patients with EBV-related stage II-IV LA-NPC by 7th edition TNM (TNM-7) treated with IMRT plus high-dose CDDP followed by adjuvant chemotherapy with CDDP/Carboplatin − 5-FU (maximum total/adjuvant CDDP-D = 540/240 mg/m 2 ) between 2003 and 2016 were analyzed. 5-year overall survival (OS) and recurrence-free survival (RFS) were calculated and compared using log-rank test by stage, adjuvant chemotherapy (yes/no) and total CDDP-D (>300 vs ≤300 mg/m 2 ). Multivariable analysis (MVA) was performed to identify survival predictors. Results: A total of 312 patients were evaluated: TNM-7 stage II/III/IV = 2%/51%/47%; T4 = 36%; N3 = 17%; adjuvant chemotherapy = 83% (79% 21% CDDP/carboplatin); median total/adjuvant CDDP-D = 380/160 mg/m 2 ; median follow-up 76 years (range 06–149). 5-year OS differed by stage II–III vs IV (95% vs 80%, p  < 0.001) and by total CDDP-D >300 (n = 210) vs ≤300 (n = 102) mg/m 2 (89% vs 83%, p =  0.02). Adjuvant chemotherapy and total CDDP-D impacted on 5-year OS in stage IV but not stage II–III. 5-year RFS was higher in stage IV patients with total CDDP-D >300 vs ≤300 mg/m 2 (74% vs 59%, p =  0.03), with a trend seen in locoregional (LRC) (91% vs 80%, p =  0.05) but not distant control (DC) (78% vs 72%, p =  0.36). Conclusions: Adjuvant chemotherapy and total CDDP-D >300 mg/m 2 improved OS and RFS in stage IV but not stage II–III LA-NPC, mainly due to effect on LRC rather than DC.